(روایات سیرت میں امام بلاذری کے ماخذ و مصادر (انساب الاشراف کی روشنی میں خصوصی مطالعہ: Sources of imam Baladhuri in Seerah Traditions (A special study in the light of Ansab-ul-Ashraf) - Munir Ahmad Qazi, Munir Ahmad Qazi (Al-Amīr Research Journal for Islamic Studies, 2024)
Ansab-ul-Ashraf is one of the most prominent works of Ahmad Bin Yahya Bin Jabir al- Baladhuri, a muslim historiographer of third Hijri Century. This book is, in fact, a genealogical form of writing history and a primary and authentic source of the Holy biography of the Holy Prophet Muhammad(ﷺ). This article comprises the life, works and especially the sources of Seerah in Ansab-ul-Ashraf. In this research article, all the sources primary and secondary from which the writer has narrated the seerah traditions have been described in brief. In the article, it has been assured that how many of the sources the writer has mentioned in his book Ansab ul Ashraf. Furthermore the authenticity and credibility of the said sources has been discussed with references. Keywords: prominent, authenticity, credibility, sources, seerah traditions.